2015
DOI: 10.1177/0963662515607406
|View full text |Cite
|
Sign up to set email alerts
|

Can citizen science enhance public understanding of science?

Abstract: Over the past 20 years, thousands of citizen science projects engaging millions of participants in collecting and/or processing data have sprung up around the world. Here we review documented outcomes from four categories of citizen science projects which are defined by the nature of the activities in which their participants engage - Data Collection, Data Processing, Curriculum-based, and Community Science. We find strong evidence that scientific outcomes of citizen science are well documented, particularly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
566
0
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 695 publications
(598 citation statements)
references
References 25 publications
9
566
0
23
Order By: Relevance
“…Scientific data and findings can be communicated to participants through projects blogs, forums, and Facebook pages, which also serve as platforms for participants to discuss their findings, raise new questions, and interact with scientists (Golumbic 2015;Jackson et al 2016). Bonney et al (2015) discuss the ability of citizen science to contribute to democratizing science and promoting a two-way dialogue between citizens and scientists. This dialogue, also termed as Public Engagement with Science (PES), emphasizes democratizing science, determining public desires and needs, encouraging transparency, and encouraging collective decision making (Brossard and Lewenstein 2009).…”
Section: Reciprocalitymentioning
confidence: 99%
“…Scientific data and findings can be communicated to participants through projects blogs, forums, and Facebook pages, which also serve as platforms for participants to discuss their findings, raise new questions, and interact with scientists (Golumbic 2015;Jackson et al 2016). Bonney et al (2015) discuss the ability of citizen science to contribute to democratizing science and promoting a two-way dialogue between citizens and scientists. This dialogue, also termed as Public Engagement with Science (PES), emphasizes democratizing science, determining public desires and needs, encouraging transparency, and encouraging collective decision making (Brossard and Lewenstein 2009).…”
Section: Reciprocalitymentioning
confidence: 99%
“…Citizen science is a broad form of cooperation between professional scientists and the public (Bonney et al 2016), which is in theory open to anyone willing to participate. However, experience has shown that different segments of the population are more prone to participate than others (Soleri et al 2016).…”
Section: Who Is the Citizen Scientist?mentioning
confidence: 99%
“…La "ciencia ciudadana" se concibe como la participación de personas no-expertas en investigaciones científicas de toda índole, y esta puede adoptar diversas formas partiendo desde la recolección de datos, pasando por el procesamiento de información, hasta la cocreación ciudadana de datos para injerir en las decisiones políticas de autoridades en favor de colectivos y comunidades locales -también llamado por "community science" (Bonney et al 2015).…”
Section: Self-tracking Como Motor De Ciudadanos 'Activos' Y 'Aumentados'unclassified